Occurrence of the R-phase with increased stability induced by low temperature precipitate-free aging in a Ni50.9Ti49.1 alloy. (1st April 2022) - Huo, Xinyu; Chen, Peng; Lahkar, Simanta; Jin, Mingjiang; Han, Xiaocang; Song, Yuanwei; Wang, Xiaodong
Abstract: The R-phase transformation presents low thermal hysteresis, high stability against thermal cycling and ultrahigh internal friction (IF). However, a clear explanation for the occurrence of the R-phase after low temperature aging and systematic characterization of the condition are still lacking. In this study, the evolution of the phase transformation behaviors and IF values after aging at 250 °C for different times are investigated in a Ni50.9 Ti49.1 alloy. Direct experimental evidence for the microstructure evolution of the B2 phase and the corresponding R-phase is provided utilizing in-situ transmission electron microscopy (TEM) techniques, together with geometric phase analysis (GPA). The reason for the occurrence of a nanodomain-structured R-phase after low temperature precipitate-free aging and the mechanism of ultrahigh intrinsic IF are illustrated. The results show that Ni segregation indicated by the localized strain fields is responsible for the formation of the R-phase after low temperature aging. Longer aging time causes larger element heterogeneity in the matrix, as a result, a wider existing temperature window for the R-phase. The ultrahigh intrinsic IF plateaus (IFInt = 0.120 ∼ 0.183) found in NiTi shape memory alloys (SMAs) are predominantly determined by the volume fraction of nanodomain boundaries. These findings provide basic insights into the R-phase formation mechanism and provide a simple way to adjust ultrahigh IF performance suitable for different application scenarios. Graphical abstract: Image, graphical abstract